2022
DOI: 10.3390/pharmaceutics14102176
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the Microbial Contamination of the Dropper Tip and Cap of In-Use Eye Drops, the Associated Contributory Factors, and the Risk of Infection: A Past-30-Years Literature Review

Abstract: The sterility of eye drop content is a primary concern from manufacturing until opening, as well as during handling by end users, while microbial contamination of the dropper tip and cap are often disregarded. The contamination of these sites during drug administration represents a risk of microbial transmission and ocular infection. In this review, we aim to assess microbial contamination of the dropper tip and cap of in-use eye drops, the associated contributory factors, and the risk of infection. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
0
7
0
1
Order By: Relevance
“…Contaminations may also cause severe infections. Contaminated trypan blue has led to endophthalmitis, and contaminated steroid and glaucoma drops and contact lens solutions have been associated with infectious keratitis . Artificial tears have not yet been associated with keratitis, although contamination has been reported …”
mentioning
confidence: 99%
“…Contaminations may also cause severe infections. Contaminated trypan blue has led to endophthalmitis, and contaminated steroid and glaucoma drops and contact lens solutions have been associated with infectious keratitis . Artificial tears have not yet been associated with keratitis, although contamination has been reported …”
mentioning
confidence: 99%
“…These infections may be due to contamination during manufacturing or, more often, while the patient uses them. 16,17 Infections with SED are possible, but we have not found such a case in NZ or in published literature despite the fact that eyes with OSD may be at particular risk. Stringent processes, including filtration, and bacterial culture before release, are generally used to manufacture SED.…”
Section: Discussionmentioning
confidence: 67%
“…Numerous studies have reported the rate of contamination of various ocular medications at different settings of drop administration, the effect of preservatives on bottle sterility, and the effect of duration of usage on the rate of contamination. The microbial contamination rate of eye drops varied from 2.3% to 73% . Contamination of the dropper tip of a multidose formulation drop is more common than contamination of the residual content of the bottle.…”
mentioning
confidence: 99%
“…Contamination of the dropper tip of a multidose formulation drop is more common than contamination of the residual content of the bottle. Multidose preservative-free formulations have a higher risk of contamination compared with eye drops with preservatives . Educating patients on the appropriate use of eye drops should reduce the risk of bottle tip contamination, especially in multidose preservative-free formulations.…”
mentioning
confidence: 99%